Action research and soft systems methodology for studying problems in emergency care delivery. (17th December 2009) - Rosmulder, Remco; Krabbendam, Koos; Kerkhoff, Toon; Luitse, Jan
This article describes the use of action research (AR) and soft systems methodology (SSM) for studying and taking action in complex and unstructured problem situations. Drawing from AR and SSM principles, it proposes a research methodology to study and improve problematic flows of patients in emergency departments using operations management concepts. Three examples illustrate the methodology: analysis and improvement actions in acute radiology service, the design and introduction of a central status board and tests of an advanced triage system. This article concludes that an action mode of research is worthy of being pursued further, in emergency departments and beyond.